The effect of repeated welding cycles on the properties of 25Cr super duplex stainless steel by automatic orbital TIG welding - Mauliddin, D.S. (Asian Research Publishing Network, 2016)
The main attention of this research is to evaluate welding properties of 25Cr Super Duplex Stainless Steel (SDSS) or also classified as UNS S32750 under repeated welding cycles with the main properties, i.e. hardness and tensile strength. The research is utilized tubing test specimen and weld by automatic orbital TIG. A small bore tubing with size diameter of 9.53 mm and thickness of 2.1mm are welded at the heat input of 0.248 kJ/mm. This process requires no filler metal and bevel end preparation since it will directly melt down two opposites edge of base metals. Welding was positioned at 2G horizontal, DCEN polarity and 99.99 Argon gas for the shield and purge. Test specimens are evaluated to simulate repeated weld cycles of original welding, R1, R2, and R3, respectively. The result shows an increase in number of repeated welding cycles will affect the ultimate tensile strength (UTS), yield strength and hardness properties. A correlation between each result and number of welding cycles is summarized into a line chart. Â© 2006-2016 Asian Research Publishing Network (ARPN).